Vacuum – assisted closure in neurosurgery as treatment option for purulent wounds after spinal implants procedures – short preliminary report - Siedlecki, Zygmunt; Hadzik, Kajetan; Woźniak, Jakub; Śniegocki, Maciej (Journal of Education, Health and Sport, 2022)
We present a short preliminary report about the use of vacuum - assisted closure in infected and purulent wounds treatment after neurosurgical spinal procedures. Our report is based on the currently treated patients and points out to other neurosurgeons this therapeutic possibility. We are currently treating two severely injured patients in bad functional state. These patients had severe spine injuries and were therefore treated surgically by decompression and fusion. Patient No. 1 had C5 burst fracture treated by anterior and posterior stabilization, while patient No. 2 had Th4 burst fracture treated with posterior transpedicular stabilization. The patients developed purulent surgical site infection. Revision and wounds irrigation were ineffective. Desire to leave titanium implants in patient’s spines (which is important for future rehabilitation), it was decided to use V.A.C® in wounds healing. We find that vacuum - assisted closure appears to be of significant benefit in such treatment. It is a good therapeutic option in the management of such patients; however, this issue requires more extensive research in the future.